Dominance or deceit: The role of the Dark Triad and hegemonic masculinity in emotional manipulation. (1st November 2020) - Waddell, Chloe; Van Doorn, George; March, Evita; Grieve, Rachel
Abstract: People may emotionally manipulate others in an attempt to control them and achieve personally satisfying outcomes. Experiencing emotional manipulation is related to several negative outcomes (e.g., depression). As a first step in addressing these negative outcomes, this study explored the utility of hegemonic masculinity and the Dark Triad (i.e., trait narcissism, Machiavellianism, and psychopathy) in predicting emotional manipulation. Three hundred and twenty-seven participants (119 men, 208 women) completed an online survey measuring hegemonic masculinity, narcissism, psychopathy, Machiavellianism, as well as their (a) perceived ability to emotionally manipulate others, and (b) willingness to engage in emotional manipulation. Hierarchical regression analyses revealed that, for both men and women, hegemonic masculinity was a significant predictor of one's willingness and perceived ability to emotionally manipulate others. However, when Dark Triad traits were added to the model, hegemonic masculinity's contribution became non-significant. Hegemonic masculinity seems to share variance with Dark Triad traits, particularly Machiavellianism. These findings are important as they establish that existing operational definitions of hegemonic masculinity share features with certain 'dark' personality traits. Thus, when predicting antisocial behaviour and tendencies, perhaps the variance explained by hegemonic masculinity is better captured by dark personality traits. Highlights: Study assesses Dark Triads contribution to emotional manipulation over hegemonic masculinity. For both sexes, masculinity predicted emotional manipulation until Dark Triad traits were added. For men, trait Machiavellianism was the strongest predictor in the final model. For women, all dark traits were significant positive predictors of emotional manipulation.